Exploration of the Role of Mathematical Connections in Developing Creative Thinking Ability: A Study on Problem-Based Learning - Nurfaida Tasni; Andi Syukriani; Hamzah Upu (PT ARRUS Intelektual Indonesia, 2026)
This study aims to explore the role of mathematical connections in developing students' creative thinking abilities through problem-based learning. The research used an exploratory qualitative approach with a case study design involving 6 purposively selected Grade XI high school students. Research instruments included a mathematical connection ability test, a mathematical creative thinking test, observation sheets, semi-structured interview guidelines, and documentation of student work. Data analysis was conducted through data reduction, data display, and conclusion drawing with triangulation techniques. The results indicate that mathematical connections play a significant role in developing creative thinking through three mechanisms: (1) connections between mathematical topics facilitate flexibility and originality; (2) connections with real-life contexts enhance fluency and elaboration; and (3) problem-based learning creates a conducive cognitive space for building connections exploratively. Students with high mathematical connections produced solutions with creativity scores 2.3 times higher. The study recommends that educators design mathematical tasks that integrate various representations, implement scaffolding to explore relationships between concepts, and create a learning environment that encourages diverse solution strategies.